Structure and Properties of Composite Coatings with Zro2 and Tio2 Particles After Lehceb Treatment; Russian Physics Journal; Vol. 67, iss. 7 - Sedelnikova M. B. Maria Borisovna; Kashin A. D. Aleksandr Daniilovich; Uvarkin P. V. Pavel Viktorovich; Sharkeev Yu. P. Yury Petrovich; Ugodchikova A. V. Anna Vladimirovna; Luginin N. A. Nikita Andreevich; Khimich M. A. Margarita Andreevna; Ivanov K. V. Konstantin Veniaminovich (2024, 2024)
Title screen